Added value of magnetic resonance spectroscopy for diagnosing childhood cerebellar tumours. (13th October 2021) - Davies, Nigel P.; Rose, Heather E. L.; Manias, Karen A.; Natarajan, Kal; Abernethy, Laurence J.; Oates, Adam; Janjua, Umair; Davies, Paul; MacPherson, Lesley; Arvanitis, Theodoros N.; Peet, Andrew C.
Abstract : 1 H‐magnetic resonance spectroscopy (MRS) provides noninvasive metabolite profiles with the potential to aid the diagnosis of brain tumours. Prospective studies of diagnostic accuracy and comparisons with conventional MRI are lacking. The aim of the current study was to evaluate, prospectively, the diagnostic accuracy of a previously established classifier for diagnosing the three major childhood cerebellar tumours, and to determine added value compared with standard reporting of conventional imaging. Single‐voxel MRS (1.5 T, PRESS, TE 30 ms, TR 1500 ms, spectral resolution 1 Hz/point) was acquired prospectively on 39 consecutive cerebellar tumours with histopathological diagnoses of pilocytic astrocytoma, ependymoma or medulloblastoma. Spectra were analysed with LCModel and predefined quality control criteria were applied, leaving 33 cases in the analysis. The MRS diagnostic classifier was applied to this dataset. A retrospective analysis was subsequently undertaken by three radiologists, blind to histopathological diagnosis, to determine the change in diagnostic certainty when sequentially viewing conventional imaging, MRS and a decision support tool, based on the classifier. The overall classifier accuracy, evaluated prospectively, was 91%. Incorrectly classified cases, two anaplastic ependymomas, and a rare histological variant of medulloblastoma, were not well represented in the original training set. On retrospective review of conventional MRI, MRS and the classifier result, all radiologists showed a significant increase (Wilcoxon signed rank test, p < 0.001) in their certainty of the correct diagnosis, between viewing the conventional imaging and MRS with the decision support system. It was concluded that MRS can aid the noninvasive diagnosis of posterior fossa tumours in children, and that a decision support classifier helps in MRS interpretation. Abstract : High diagnostic accuracy was achieved in the prospective evaluation of a 1 H‐magnetic resonance spectroscopy (MRS) diagnostic classifier previously developed for childhood cerebellar tumours. A radiologist's diagnostic accuracy was significantly improved when standard conventional imaging was supplemented by a clinical decision support system including the MRS classifier.